1993
DOI: 10.1677/joe.0.1360059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3,3′-di-iodothyronine and 3,5-di-iodothyronine on rat liver mitochondria

Abstract: In the present study we report that 3,3',5-tri-iodothyronine (T3) as well as two iodothyronines (3,5-di-iodothyronine (3,5-T2) and 3,3'-di-iodothyronine (3,3'-T2)) significantly influence rat liver mitochondrial activity. Liver oxidative capacity (measured as cytochrome oxidase activity/g wet tissue) in hypothyroid compared with normal rats was significantly reduced (21%, P > 0.01) and the administration of T3 and both iodothyronines restored normal values. At the mitochondrial level, treatment with T3 stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 19 publications
1
38
0
1
Order By: Relevance
“…Diiodothyronines either could have different effects, or could not reach their intracellular targets when injected into animals. As previously hypothesized [15,16], T 3 could be responsible for long-lasting action of thyroid hormones, whereas diiodothyronines could be involved in rapid energetic adjustment to an altered physiological state, such as cold exposure, overfeeding etc.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Diiodothyronines either could have different effects, or could not reach their intracellular targets when injected into animals. As previously hypothesized [15,16], T 3 could be responsible for long-lasting action of thyroid hormones, whereas diiodothyronines could be involved in rapid energetic adjustment to an altered physiological state, such as cold exposure, overfeeding etc.…”
Section: Discussionmentioning
confidence: 86%
“…Concerning the lack of diiodothyronines effects on basal metabolic rate, after their administration in vivo [15,25], it is possible that plasma membranes are not permeable to diiodothyronines and that they are only formed within cells from Ts. Only after chronic treatment of hypothyroid animals, it is possible to show an effect of diiodothyronines in some tissues such as the liver, which could be more permeable to diiodothyronines [12,13], but this has only little effect on basal metabolic rate (= 10-20% stimulation) [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as mentioned before, several reports dealing with the action of iodothyronines at the cellular level, have shown that two diiodothyronines (3,3'-T2 and 3,5-TE) are the thyroid hormone analogues which are most effective at the cellular level [1][2][3][4][5][6]. In previous studies we hypothesized that T3 could be responsible for the nuclear and long-term actions of thyroid hormones and diiodothyronines for the direct mitochondrial short-term actions [1,2]. This hypothesis presupposes the presence of specific binding sites for diiodothyronines in mitochondria.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, in spite of several reports showing rapid effects of triiodothyronine (T3) on mitochondria, the occurrence and the physiological significance of these effects is a long standing controversial issue of thyroid hormone action. In recent years, however, several reports have shown that two diiodothyronines (3,3'-T2 and 3,5-T2), under certain conditions, are the only iodothyronines which rapidly stimulate in vivo and in vitro mitochondrial respiration or cytochrome oxidase (COX) activity [1][2][3][4][5][6]. At the moment, the physiological significance of these effects is not clear and no insight into the mechanism by which diiodothyronines stimulate mitochondrial energy metabolism is available.…”
Section: Introductionmentioning
confidence: 99%